Effect of mucoadhesive polymers on the in vitro performance of insulin-loaded silica nanoparticles: Interactions with mucin and biomembrane models - Andreani, Tatiana; Miziara, Leonardo [UNESP]; Lorenzón, Esteban N. [UNESP]; Souza, Ana Luiza R. de [UNESP]; Kiill, Charlene P. [UNESP]; Fangueiro, Joana F.; Garcia, Maria L.; Gremião, Palmira D. [UNESP]; Silva, Amelia M.; Souto, Eliana B. (Elsevier B.V., 2015)
The present paper focuses on the development and characterization of silica nanoparticles (SiNP) coated with hydrophilic polymers as mucoadhesive carriers for oral administration of insulin. SiNP were prepared by sol-gel technology under mild conditions and coated with different hydrophilic polymers, namely, chitosan, sodium alginate or poly(ethylene glycol) (PEG) with low and high molecular weight (PEG 6000 and PEG 20000) to increase the residence time at intestinal mucosa. The mean size and size distribution, association efficiency, insulin structure and insulin thermal denaturation have been determined. The mean nanoparticle diameter ranged from 289 nm to 625 nm with a PI between 0.251 and 0.580. The insulin association efficiency in SiNP was recorded above 70%. After coating, the association efficiency of insulin increased up to 90%, showing the high affinity of the protein to the hydrophilic polymer chains. Circular dichroism (CD) indicated that no conformation changes of insulin structure occurred after loading the peptide into SiNP. Nano-differential scanning calorimetry (nDSC) showed that SiNP shifted the insulin endothermic peak to higher temperatures. The influence of coating on the interaction of nanoparticles with dipalmitoylphosphatidylcholine (DPPC) biomembrane models was also evaluated by nDSC. The increase of AH values suggested a strong association of non-coated SiNP and those PEGylated nanopartides coated with DPPC polar heads by forming hydrogen bonds and/or by electrostatic interaction. The mucoadhesive properties of nanoparticles were examined by studying the interaction with mucin in aqueous solution. SiNP coated with alginate or chitosan showed high contact with mucin. On the other hand, non-coated SiNP and PEGylated SiNP showed lower interaction with mucin, indicating that these nanopartides can interdiffuse across mucus network. The results of the present work provide valuable data in assessing the in vitro performance of insulin-loaded SiNP coated with mucoadhesive polymers. (C) 2015 Elsevier B.V. All rights reserved.
Keywords: Silica nanoparticles; Mucoadhesion; Insulin; Oral delivery; Biomembranes; Thermal denaturation